Parties of the Shareholders’ Agreement - E. M. Bondariev (Bulletin of Kharkiv National University of Internal Affairs)
The author of the article has studied the problem of determining the subjective aspect of a shareholders’ agreement. On the basis of the analysis of the legislation of Ukraine and other countries, as well as the legal doctrine of corporate law, the author has concluded that exclusively shareholders of a particular company should be recognized as such persons, since they as the holders of subjective corporate rights, have the opportunity to exercise them in the manner determined by such an agreement.